Membangun Ekosistem Pembelajaran Digital: Analisis Kebutuhan Media Pembelajaran Biologi Bagi Siswa SMA: (Building a Digital Learning Ecosystem: An Analysis of Biology Learning Materials for High School Students) - Laili Magfiroh, Sandi; Murtini, Iin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
This study aims to analyze the necessity of Biology instructional media as a foundation for developing a digital learning ecosystem for tenth-grade students. This research employed a descriptive quantitative method. Data were collected through a validated needs-analysis questionnaire distributed to students of class X-F at SMA Negeri 5 Tuban and subsequently analyzed using descriptive percentage techniques. The results revealed that the average student need for instructional media was 75.86% (high category). Specifically, the highest demand was found in the visual and interactive media indicator at 78.8%, followed by practicum and field activities (78.4%), interest and attitudes toward Biology learning (76.9%), learning difficulties (73.3%), and the need for additional strategies and learning resources (71.9%). These findings indicate that students require not only visual and contextual learning media but also an integrated digital learning ecosystem. This study provides an empirical basis for developing adaptive, interactive, and sustainable Biology instructional media in the digital era. Abstrak. Penelitian ini bertujuan untuk menganalisis kebutuhan media ajar Biologi sebagai landasan pengembangan ekosistem pembelajaran digital bagi siswa kelas X. Jenis penelitian ini adalah deskriptif kuantitatif. Data dikumpulkan melalui kuesioner analisis kebutuhan yang divalidasi dan disebarkan kepada siswa kelas X-F SMA Negeri 5 Tuban, kemudian dianalisis menggunakan teknik persentase deskriptif. Hasil penelitian menunjukkan bahwa rata-rata tingkat kebutuhan siswa terhadap media ajar baru mencapai 75,86% (kategori tinggi). Secara spesifik, indikator kebutuhan media visual dan interaktif menduduki persentase tertinggi sebesar 78,8%, diikuti oleh kebutuhan praktikum dan aktivitas lapangan (78,4%), minat dan sikap terhadap pembelajaran Biologi (76,9%), analisis kesulitan belajar (73,3%), serta kebutuhan strategi dan sumber belajar tambahan (71,9%). Temuan ini mengindikasikan bahwa siswa membutuhkan media ajar yang tidak hanya visual dan kontekstual, melainkan juga dukungan ekosistem digital yang terintegrasi. Penelitian ini memberikan kontribusi empiris sebagai dasar pengembangan media pembelajaran Biologi yang adaptif, interaktif, dan berkelanjutan di era digital.